Tujuan Pembangungan Berkelanjutan (TPB): Hilirisasi Inovasi Teknologi Informasi dan Komunikasi menuju Independent dan Smart Village : INA - Gede Eka Putrawan; Bambang Riadi; Ryzal Perdana (LPPM Universitas Lampung, 2021)
Towards an independent and smart village that is successful, advanced, and independent, and prosperous, forms of active participation from various parties, including universities, to support the success of the program are needed. Therefore, this community service activity will be carried out in order to downstream information and communication technology innovation to go independent and smart village which will be carried out in Rukti Endah Village seputih Raman District of Central Lampung Regency. The purpose of this activity is to hold the official village page, train human resources, and digitize data and information and public services. This activity will be carried out by methods of presentation, discussion, model development, practice, and simulation. Through this activity, it is expected that partner villages will be able to improve the quality of service so that it is no longer confusing and time-consuming so that the village apparatus will not be busy with administrative problems. In addition, village data and information will be more organized so that decision making for data-driven development purposes can be done appropriately and various potential villages will be accessible to anyone and at any time. Digital village progress for the future is very good because with the smart village it is expected that the village can become independent and able to run it. The structure of the village is also important because it makes the community an important part of the development and progress of the village so that almost all village policies will always pay attention to the existence of the community.